Visualization analysis of breast cancer-related ubiquitination modifications over the past two decades - Yongxiang Li; Yiyang Wang; Yubo Jing; Youseng Zhu; Xinzhu Huang; JunYi Wang; Elihamu Dilraba; Chenming Guo (Discover Oncology)
Abstract Background Ubiquitination is a type of post-translational modification, referring to the process in which the small molecular protein ubiquitin covalently binds to target proteins under the catalysis of a series of enzymes. The process of ubiquitination is vital in the onset and progression of breast cancer. The use of the ubiquitin-protease system is expected to be a new way to treat human breast cancer. This research aimed to investigate the evolution patterns, key areas of interest, and future directions of ubiquitination in breast cancer via bibliometric analysis. Methods Research articles on ubiquitination modifications in breast cancer were sourced from the Web of Science Core Collection database and analyzed via Microsoft Excel 2021, Bibliometrix, VOSviewer, and Citespace software for thorough bibliometrics. Results From 2005–2024, 1850 English articles published in 405 journals by 1842 institutions/universities from 61 countries were included in the study. Keywords, research fields, co-cited literature and other information were included. Research on ubiquitination modifications has focused on breast cancer, expression, protein, activation, degradation, ubiquitination, phosphorylation, etc. Notably, the keywords that broke out in the past five years have focused on "triple-negative breast cancer", "promotion", and "metabolism". These findings suggest that key areas of current research are metabolism, immunity, survival, and prognosis in triple-negative breast cancer. Conclusions Our findings indicate that research on triple-negative breast cancer, as well as its immunological and metabolic aspects, is a burgeoning and promising area. Our work offers valuable guidance and fresh perspectives on the relationship between breast cancer and ubiquitin modification.